Intention to use the internet of micro-size enterprises: Evidence from the biggest emerging market in Southeast Asia - Rivai, Harif Amali; Fernando, Yudi (Inderscience Enterprises Ltd., 2019)
This study aims to examine the intention to use the internet of micro-size enterprises. A survey was conducted in Indonesia, which is one of the biggest emerging markets in Southeast Asia. The sampling includes micro-size enterprises in West Sumatra province. The data were collected from 285 business owners and managers. Structural Equation Modelling with AMOS version 21 was used for data analysis. The results showed that perceived ease of use, computer self-efficacy, and perceived usefulness as predictors of behavioural intention to use the internet. No significant influence of trust in internet technology on perceived usefulness was found, which impacts micro-size enterprises selling products and services on website. The future study therefore, need to study the effectiveness of mobile applications which are developed by micro-size enterprises as another business alternative on online business.